"Pushing me ahead before I was ready was a serious mistake!"- School memories and identity development. (2020) - Arwas, Esther; Flum, Hanoch
Highlights: Student-teacher relationship is central to identity development across the lifespan. Fit or mismatch of teacher's response to psychological needs are particularly recalled. Satisfying these needs affects lifelong identity development. Findings lend support to Erikson's identity development stage model. Adults' retrospection of school experience reveal identity development trajectories. Abstract: The long-term impact of teacher-student relationship on identity formation, as perceived retrospectively, was studied narratively using interview and Relational Space Maps (Josselson, 1992 ). A heterogeneous group of 36 Israeli adults (aged 50–60) was asked about their schooling experiences. Analysis of their narratives from a relational-developmental perspective revealed psychological "fittedness" (Erikson, 1956 ) as a central relational principle, having a critical impact on students' lifelong identity development, motivation, and achievement. The findings of this qualitative study lend support to Erikson's model of identity formation. The retrospection of individuals at middle-late adulthood underscores these important long-lasting developmental influences.